A Concept Study on Advanced Radioisotope Solid Solutions and Mixed-Oxide Fuel Forms for Future Space Nuclear Power Systems. (3rd June 2021) - Ambrosi, Richard M.; Kramer, Daniel P.; Watkinson, Emily Jane; Mesalam, Ramy; Barco, Alessandra
Abstract: Radioisotope power systems (RPSs) have transformed our ability to explore the solar system. RPSs have been in existence for almost seven decades. Most missions have utilized 238 Pu as the radioisotope of choice to generate electrical power and to produce heat for the operation and thermal management of spacecraft systems. In Europe, for the past decade 241 Am has been selected for RPS research programs. This paper hypothesizes that the inclusion of small quantities of relatively short-lived radioisotopes such as 232 U and 244 Cm, particularly when dealing with long-lived radioisotope 241 Am, could have beneficial implications for future RPS designs. This paper focuses on the thermal output implications and impact on system-level design. The authors recognize that the selection of any new or modified radioisotope heat source material will require extensive research on fuel form stability, the radiological impact, cost of production, containment, and launch safety considerations.